Role of different organic and inorganic amendments in the biofortification of iodine in Coriandrum sativum crop - Tianyi, Yan; Farooq, Ambar; Mohiuddin, Muhammad; Farooq, Asma; Gonzalez, Norela C. T.; Abbasi, Asim; Hina, Aiman; Irshad, Muhammad (Frontiers in Ecology and Evolution, 2023)
Iodine Deficiency Disorder (IDDs) is one of the mountainous communities' most prevailing and common health issues. An effective way to control the prevalence and emergence of IDDs in remote areas can be using iodized salt. However, recent studies indicated that most of the iodized salt had been lost during the cooking process. The current study of iodine biofortification differed from the previous studies in two main aspects: it involved exogenous organic Iodine (OI), and inorganic Iodine (KI) added in the amended soils, which previous studies did not consider. Moreover, the translocation, transformation, and distribution of Iodine from soil to plants are poorly understood in amended soil. Thus, identifying an effective management option to enhance iodine (I) bioavailability in nutrient-deficient soils is currently a significant challenge. Therefore, a greenhouse study was conducted to investigate the effects of organic and inorganic soil amendments on the uptake of different iodine sources in coriander crop. Results showed that applying an inorganic iodine source significantly enhanced the iodine edible part of the crop compared to the control (p < 0.05). The application of soil amendments relatively improved Iodine uptake by the coriander crop compared to the control. The highest Iodine was found in crop tissues grown in wood ash-amended soil supplemented with KI (291.97 µg kg-1). The KI uptake was significantly higher than the OI (p < 0.05). Compared to OI, a higher translocation factor (0.96) and distribution coefficient (3.51) were found for plants treated with KI. Thus, this study indicated that a suitable soil amendment could be a better option for Iodine biofortification and serve as an alternative to iodized salt for preventing IDDs.